Inspiration to mRNA-based COVID-19 vaccination: Serious adverse case reports with hepatitis B vaccine in real-world - Lu, Jinmiao; Zhang, Xunjie; Xu, Hong; Li, Zhiping (Frontiers in Pediatrics, 2022)
Objectives: The hepatitis B vaccine comprises hepatitis B surface antigen (HBsAg) produced by transgenic yeast cells. There are few serious adverse events (SAE) reports after Hepatitis B vaccination. Methods: The authors searched the Chinese legal documents database for all SAE with Hepatitis B vaccination from January 2010 to January 2022. Results: All seven patients received yeast-derived recombinant hepatitis B vaccine. Three cases of myocarditis (death), 2 cases of interstitial pneumonia (death), and 2 cases of encephalitis. The mean time of onset of SAE was 8.3 ± 4.3 hours after vaccination. Conclusion: Patients need to be aware that the second dose of the hepatitis B vaccine is associated with a higher risk of SAE than the first dose. The mechanism of vaccine-induced myocarditis may come from immune protein reactions. Based on the experience of Hepatitis B vaccine adverse events, we present new insights into the mechanism of myocarditis caused by the COVID-19 vaccine.